2012
DOI: 10.1002/ajmg.a.35487
|View full text |Cite
|
Sign up to set email alerts
|

Isodicentric Y chromosomes in Egyptian patients with disorders of sex development (DSD)

Abstract: Isodicentric chromosome formation is the most common structural abnormality of the Y chromosome. As dicentrics are mitotically unstable, they are subsequently lost during cell division resulting in mosaicism with a 45,X cell line. We report on six patients with variable signs of disorders of sex development (DSD) including ambiguous genitalia, short stature, primary amenorrhea, and male infertility with azoospermia. Cytogenetic studies showed the presence of a sex chromosome marker in all patients; associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…Speroff et al [1999] stated that typical mixed gonadal dysgenesis is characterized by the presence of a streak gonad on one side and a dysgenetic or normally appearing testis on the other side with subsequent müllerian and/or wolffian duct development. The most common karyotype of ovotesticular DSD is 46,XX, but other karyotypes were also reported like 46,XX/47,XXY [Ozsu et al, 2013] and 45,X/46,X,idic(Y) [Tran et al, 2011;Mekkawy et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speroff et al [1999] stated that typical mixed gonadal dysgenesis is characterized by the presence of a streak gonad on one side and a dysgenetic or normally appearing testis on the other side with subsequent müllerian and/or wolffian duct development. The most common karyotype of ovotesticular DSD is 46,XX, but other karyotypes were also reported like 46,XX/47,XXY [Ozsu et al, 2013] and 45,X/46,X,idic(Y) [Tran et al, 2011;Mekkawy et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…45,X chromosome mosaicism with Y chromosomal material is considered among the principle causes of ambiguous genitalia [Smith et al, 1996;Mekkawy et al, 2012]. The presence or absence of the SRY gene as well as other genomic sequences is involved in marked phenotypic diversity [Ogata, 2002;Abdelmoula and Amouri, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…1 a). Similarly, Jakubowski et al [2000], Caglayan et al [2009] and Mekkawy et al [2012] reported male infants with MGD who had ambiguous genitalia and idic(Yp) abnormalities but in a high population of lymphocytes. It was suggested that the presence of a double dose of the SRY gene initiated male sexual development, but the existence of a 45,X cell line affected the threshold of SRY expression needed to establish adequate testicular differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Isodicentrics are considered the most common structural abnormality of the Y chromosome [Hsu, 1994;Quilter et al, 2002] and are explained by the occurrence of a single break, followed by fusion of the broken ends of sister chromatids and the loss of the acentric fragment during gametogenesis before spermatid formation [Quilter et al, 2002]. They are usually unstable during cell division, generating various types of cell lines, mainly including 45,X, leading to variable somatic features and different gonadal histopathologic findings [DesGroseilliers et al, 2006;Mekkawy et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation